Development of Branching Programmed Learning Media for Science Subjects - Anesia Anesia; Indrati Kusumaningrum; Jasrial Jasrial; Darmansyah Darmansyah (Postgraduate, University of Mataram, 2023)
The background of this study is the results of observations on science learning at MTsN 3 Tanjung Jabung Barat, which show that the science learning process has not been able to create effective learning activities to obtain essential competencies, and the learning resources used are not enough to motivate students and support the content in explaining science concepts. The study aims to develop branching programmed learning media, which can increase the motivation and learning outcomes of class VIII MTs students for science subjects on the topic of vibrations, waves and sound. This type of research is development research that refers to the ADDIE model. The results show that the branching programmed learning media in science subjects has met the valid, practical, and effective criteria in increasing the experimental group's average value of learning outcomes by 85.37. In contrast, the control group obtained a mean score of 73.89. The results of hypothesis testing at a significant level of É‘ 0.05 show t count 5,484 > t table 2,007 which means there are significant differences in the average value of learning outcomes between the control and experimental group. Based on the results of research, the branching programmed learning media meets the valid, practical, and effective criteria to be used as a learning resource for science subjects.